Perilaku Prososial ditinjau dari Religiusitas pada Siswa Kelas VII di Sekolah Swasta di Kudus - Nurul Izzatil Khusna; Anita Aisah (Jurnal Education and Development, 2023)
The beginning of teenage hood in grade VII students is a transition period from childhood to adulthood by considering the physical, biological and psychological aspects in social life. Based on preliminary studies, there are new students entering the new school level that makes them interested in expanding friendships, until gradually over time there is a selfish attitude of each student that makes the friendships lead to hostility. The purpose of this study is to analyze whether there is an influence of religiosity on the prosocial behavior of grade VII students of Madrasah Tsanawiyah Ma'ahid Kudus. This study used quantitative research. The population of 243 students with a sample of 151 students was selected using a simple random sampling technique. The instrument was religiosity on the scale of prosocial behavior. The data were analyzed with simple linear regression. The data showed that the students’ religiosity was in the moderate category at 66%. Meanwhile, the prosocial behavior of the students was in the moderate category with a percentage of 66%. There was a result of 0.000 ≤ 0.05 meaning that there was a significant influence with data that by 32.3%, religiosity influenced students' prosocial behavior and the remaining 67.7% was influenced by other factors. The results showed that there was a significant influence of religiosity on the prosocial behavior of grade VII students of Madrasah Tsanawiyah Ma'ahid Kudus